Implicit theories of women preschool pre-service teachers and emotional intelligence - Gutiérrez-Cobo, María José; Cabello, Rosario; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2023)
Introduction. Pre-service teachers should be prepared to face the emotionally demanding situations associated with the profession. The previous literature suggests that two variables are important for managing teaching demands: emotional intelligence (EI) or the ability to perceive, facilitate, understand, and manage emotions and implicit theories (ITs). ITs refer to the beliefs about the malleability of various life domains. Individuals can be divided into incremental theorists (believing that attributes are malleable) and entity theorists (attributes are fixed). Objective. This study aimed to evaluate the influence of ITs of intelligence and EI on self-report and ability EI in a sample of female pre-school pre-service teachers. Method. 224 participants (M= 21.27, SD = 4.72) were assessed on ability EI (performance and self-report instruments), ITs of intelligence, ITs of EI, age, and parental education. Results. In our sample, incremental EI -but not intelligence -theories predicted higher scores on self-report and ability EI. In particular, being an incremental theorist of EI predicted 11% and 20% of the variance of the global EI and the managing branch of the ability EI, respectively. Conclusion. Our findings suggest the importance of ITs of EI for pre-service teachers' Emotional Intelligence and open the door to implementing ITs of EI training in this population. These theoretical and practical implications are discussed.